Os paradigmas concorrenciais do setor de transporte aéreo: uma análise sobre as estratégias da companhia aérea Air France - Ana Paula Camilo Pereira (Confins)
Airlines companies largely produce the numerous and incessant transformations in the worldwide civil air transport sector. At the same time, they are the agents more susceptible to macroeconomic changes of the dynamism of this market. In this perspective, this paper proposes to achieve an approach to the paradigms of competition in the airline sector, emphasizing the strategic actions of Air France, as from an analysis that considers association between territorial dynamics and dynamics of capital. In that sense, it emphasizes the faces overlapped in the competition of airline sector, and with this we aim to demystify the intentionality of strategies that simulate a sector widely coated of rivalry between airlines companies. Thus, there are strategic actions of Air France some factors that define this market currently and represent the guiding elements of a competition organization that occurs around the standards imposed by the process of globalization.